Synergistic activity of the combination of falcarindiol and itraconazole in vitro against dermatophytes - Kan, Siyue; Tan, Jingwen; Cai, Qing; An, Lulu; Gao, Zhiqin; Yang, Hong; Liu, Siyu; Na, Risong; Yang, Lianjuan (Frontiers in Cellular and Infection Microbiology, 2023)
Previous studies have shown that natural polyacetylene alcohols, such as falcarindiol (FADOH), have good antifungal effects on plant fungi. While its effect on fungi that infect humans remains to be explored. In our study, checkerboard microdilution, drop-plate assay, and time-growth method were employed to analyze the interactions between FADOH and itraconazole (ITC) in vitro against dermatophytes, including 12 Trichophyton rubrum (T. rubrum), 12 Trichophyton mentagrophytes (T. mentagrophytes), and 6 Microsporum canis (M. canis). The results showed that the combination of FADOH and ITC exhibited synergistic and additive activity against 86.7% of all tested dermatophytes. FADOH had an excellent synergistic effect on ITC against T. rubrum and T. mentagrophytes; the synergistic rates were 66.7% and 58.3%, respectively. On the contrary, FADOH combined with ITC showed poor synergistic inhibitory activity (16.7%) against M. canis. Moreover, the additive rates of these two drugs against T. rubrum, T. mentagrophytes, and M. canis were 25%, 41.7%, and 33.3%, respectively. No antagonistic interactions were observed. The drop-plate assay and time-growth curves confirmed that the combination of FADOH and ITC had a potent synergistic antifungal effect. The in vitro synergistic effect of FADOH and ITC against dermatophytes is reported here for the first time. Our findings suggest the potential use of FADOH as an effective antifungal drug in the combined therapy of dermatophytoses caused especially by T. rubrum and T. mentagrophytes.